Study on the production of hydrogen gas from water electrolysis on motorcycle engine - Zikri Zikri; Aken Derisman; Muslim Muslim; Wawan Purwanto; Al Ichlas Imran (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2022)
The primary emphasis of the research is on how to use hydrogen as an energy source for motorcycle fuel. This is an intriguing hypothesis to explore since, at the moment, fossil energy is used to meet fuel demands, although fossil energy supplies are running limited. As a result, hydrogen energy is an option that may be employed as a fuel substitute utilizing commercial water raw materials and the electrolysis method. The research goal is to demonstrate that electrolysis of water to hydrogen gas may occur while the vehicle is in use, to compute the amount of hydrogen gas generated, and to determine the time the vehicle can be utilized using the gas fuel created. The long-term goal of this study is to create a vehicle powered entirely by hydrogen gas produced by water electrolysis, particularly for motorcycles. The experimental approach was employed in this investigation, with three phases of testing on a carburetor-type motorbike utilizing 1, 2, and 3 liters of Pertamax gasoline. The results demonstrated that the process of electrolysis of water into hydrogen gas on motorcycles is possible; however, the amount of gas generated is still quite little. The hydrogen gas generated by this electrolysis method is only 0.06 bar when 1 liter of fuel is used, 0.42 bar when 2 liters of fuel are used, and 0.98 bar when 3 liters of fuel are used.